Hippocampal area CA2 activity supports social investigation following an acute social stress - Radzicki, Daniel; McCann, Katharine E.; Alexander, Georgia M.; Dudek, Serena M. (Molecular psychiatry, 2025)
Neuronal activity in the hippocampus is critical for many types of memory acquisition and retrieval and influences an animal’s response to stress. Moreover, the molecularly distinct principal neurons of hippocampal area CA2 are required for social recognition memory and aggression in mice. To interrogate the effects of stress on CA2-dependent behaviors, we chemogenetically manipulated neuronal activity in vivo during an acute, socially derived stressor and tested whether memory for the defeat was influenced. One day after an acute social defeat (aSD), defeated mice spent significantly less time investigating another mouse when compared to non-defeated control mice. We found that this avoidant phenotype persisted for up to one month following a single defeat encounter. When CA2 pyramidal neuron activity was inhibited with Gi-DREADD receptors during the defeat, subject mice exhibited a significantly higher amount of social avoidance one day later when compared to defeated littermates not expressing DREADDs. Moreover, CA2 inhibition during defeat caused a reduction in submissive defense behaviors in response to aggression. In vitro electrophysiology and tracing experiments revealed a circuit wherein CA2 neurons connect to caudal CA1 projection neurons that, in turn, project to corticolimbic regions including the anterior cingulate cortex. Finally, socially avoidant, defeated mice exhibited significant reductions in cFos expression in caudal hippocampal and limbic brain areas during a social investigation task 24 h after aSD. Taken together, these results indicate that CA2 neuronal activity is required to support behavioral resilience following an acute social stressor and that submissive defensive behavior during the defeat (vs. fleeing) is a predictor of future resilience to social stress. Furthermore, CA2 preferentially targets a population of caudal CA1 projection neurons that contact cortical brain regions where activity is modulated by an acute social stressor.